PENERAPAN KONSELING REALITA UNTUK MENURUNKAN INTENSITAS PERILAKU AGRESIF PADA SISWA KELAS XII IPS 2 Dl SMAN 1 JENGGAWAH KABUPATEN JEMBER TAHUN PELAJARAN 2015/2016 - Dodik Wahyu Triyono; Arifin Nur Budiono; Siti Rahayu (FKIP Universitas Islam Jember, 2016)
The primary aim of this present study is to investigate the effectiveness of reality approach to counselling on humans aggressive behavioral change. This is a counseling action research. This comprises of four phases namely acting, planning, observing, and reflecting. The subjects of this study were 36 students of SMAN 1 Jenggawah in the 2015/2016 academic year. Questionnaire and documentation are used to gather the data. In analysing the data, the researcher employs data reduction, data display and, lastly, conclusion drawing/verification. After treated by reality counceling services, the findings indicated that there was a steady decrease of verbal aggressive behavior displayed by the students of class XI IPS 2 at SMA Negeri 1 Jenggawah. In addition, the result also showed that the average of verbal aggressive behavior also fell. It could be shown from the score gained by the students, 67 – 94 of 60% overall score.Keywords: Aggressive Behavior, Reality counseling services, verbal aggressive behavior.